Genetic analysis of protein content and oil content in soybean by genome-wide association study - Jin, Hui; Yang, Xue; Zhao, Haibin; Song, Xizhang; Tsvetkov, Yordan Dimitrov; Wu, YuE; Gao, Qiang; Zhang, Rui; Zhang, Jumei (Frontiers in Plant Science, 2023)
Soybean seed protein (PC) and oil contents (OC) have important economic value. Detecting the loci/gene related to PC and OC is important for the marker-assisted selection (MAS) breeding of soybean. To detect the stable and new loci for PC and OC, a total of 320 soybean accessions collected from the major soybean growing countries were used to conduct genome-wide association study (GWAS) by resequencing. The PC ranged from 37.8% to 46.5% with an average of 41.1%, and OC ranged from 16.7% to 22.6% with an average of 21.0%. In total, 23 and 29 loci were identified, explaining 3.4-15.4% and 5.1-16.3% of the phenotypic variations for PC and OC, respectively. Of these, 8 and 5 loci for PC and OC overlapped previous reported loci, and the other 15 and 24 loci were newly identified. In additionIn addition, nine candidate genes were identified which are known to be involved in protein and oil biosynthesis/metabolism including lipid transport and metabolism, signal transduction and plant development pathway. These results uncover the genetic basis of soybean protein and oil biosynthesis and promote the progresses for enhancing soybean PC and OC.